Dinâmica do mercado de crédito imobiliário no Brasil - Marques, Francisco Leovanni de Sousa (2023)
The study carried out tends to demonstrate that market concentration produces negative effects on the interest rate in real estate financing lines for individuals, while deconcentration has the opposite effect, expanding the supply environment and producing an effect contrary to that of concentration, reducing levels of rates available and offered in said lines of credit. On this aspect, we seek to prove through the use of market concentration measures that it becomes possible to identify the dominance that economic agents exercise in their sector of activity, knowing that these concentration measures also take into account the number of companies in the market. market and the inequality of participation in the market niche. In addition, the concentration measures are intended to capture the degree of market power of each company and/or institution, that is, it verifies the capacity that a firm has to control the sale price of a product or service, and in the ca se of this study, the interest rate applied on the real estate financing credit operation to the final consumer. Of the various concentration measurement models that are available, the Index C5 and the HHI (Hirchsman Herfindahl Index) were used as indicato rs for assessing the impact generated by concentration or deconcentration on the average interest rate of these credit operations. By estimating the parameters through econometric models and making the final calculation of the results, it was found that th ere is an improvement in the rate levels when there is a market environment of deconcentration.